Analisis Tingkat Kepatuhan Wajib Pajak Umkm dalam Pelaporan SPT Tahunan Setelah Berlakunya PP No. 23 Tahun 2018 (Studi Pada KP2KP Baradatu) - Lailani Gita Fania; Yulianto Yulianto; Simon Sumanjoyo Hutagalung (Jurusan Ilmu Administrasi Publik FISIP Universitas Lampung, 2021)
Tax is the most source of financing for development in Indonesia. The tax reformation make policy and administration more comphrehensive by Directorate General of Taxes. The expectation of The tax reformation could be increase compliance of taxpayer. The rise of UMKM almost five years in District Way Kanan make Way Kanan has good potential in taxtation. In 2018 The governance has realeased regulation, it is PP No. 23 Th. 2018. The regulation about tariff reduction for UMKM, the rate reduction of 0,5%. Aim of this regulation is taxpayers get easier for do some taxation include to report tax return every year, to encourage taxpayers get into formal economics, and to give taxpayers a sense of justice. The research aim get to know how much tariff reduction influence toward to increase compliance of taxpayer about report the tax return in every year in District Way Kanan. The research applies quantitative approach and descriptive method. The research applies data collection technique by questionnaire, document, and observation. The data analysis technique by simple analysis tabulation, validy test, reliability test, normalitiy test, correlation test, determinasi coefficient test, simple linear regression test, and hypotheses test. The result of this study is that hypotheses of this study is accepted and be found how much influence tariff reduction influence toward to increase compliance of taxpayer about report the tax return in every year in District Way Kanan is 18,2%.